Faculty appointments and the record of scholarship - Brand, Amy (eLife, 2013)
Academic review committees would benefit from more details about the contributions made by individual researchers to papers with multiple authors, and also from more information about other types of scholarly communication.
Keywords: Point of view; publishing; academic career; contributorship; ORCID